2021
DOI: 10.1371/journal.pone.0255119
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the geographic specificity of pH prediction by classification and regression trees

Abstract: Soil pH effects a wide range of critical biogeochemical processes that dictate plant growth and diversity. Previous literature has established the capacity of classification and regression trees (CARTs) to predict soil pH, but limitations of CARTs in this context have not been fully explored. The current study collected soil pH, climatic, and topographic data from 100 locations across New York’s Temperate Deciduous Forests (in the United States of America) to investigate the extrapolative capacity of a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…However, some studies showed that CART has better performance for pH, compared with RF [60,68]. When the interpretability of the resulting model is important for the user, logical-based machine learning models are more appropriate, as they do not function as "black boxes" [69], and the main advantage is that the former provides an estimate of the relative importance of the predictors in the model, and avoids the elimination of predictive covariates that may be relevant for soil, even if there are correlations between them [70].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that CART has better performance for pH, compared with RF [60,68]. When the interpretability of the resulting model is important for the user, logical-based machine learning models are more appropriate, as they do not function as "black boxes" [69], and the main advantage is that the former provides an estimate of the relative importance of the predictors in the model, and avoids the elimination of predictive covariates that may be relevant for soil, even if there are correlations between them [70].…”
Section: Discussionmentioning
confidence: 99%